A high-nickel precursor and preparation method thereof, positive electrode material, secondary battery and electrical equipment

By preparing high nickel precursors with high nickel molar amount and large specific surface area, the problem of degradation of cycling and safety performance of the positive electrode material is solved, and higher energy density and more stable cycling performance are achieved.

CN119735247APending Publication Date: 2025-04-01GUANGXI CNGR NEW ENERGY SCI & TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311258159.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The circulation performance and safety performance of the lithium-ion battery positive electrode material produced by the high nickel precursor system are reduced.

Method used

A high nickel precursor is provided, with a ratio of nickel moles to total metal moles in 90%-100%, and a specific surface area of ​​25m2/g-70m2/g. By adjusting reaction conditions such as temperature, pH value and solution flow, secondary particles with porous structure are prepared.

Benefits of technology

The energy density and capacity performance of the positive electrode material are improved, and the consistency of the crystal structure is maintained by reducing the sintering temperature, which improves the circulation performance and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735247A_ABST
    Figure CN119735247A_ABST
Patent Text Reader

Abstract

The present application provides a high-nickel precursor and a preparation method thereof, a positive electrode material, a secondary battery and an electrical device. The ratio a of the molar amount of nickel to the total molar amount of metal contained in the high-nickel precursor is 0.90-1.00; the specific surface area BET of the high-nickel precursor is 25m 2 / g‑70m 2 / g. The high nickel precursor provided in the present application has a large specific surface area, indicating that it has a porous structure, so when the positive electrode material is prepared from it, it is beneficial to promote the sintering mass transfer process of the high nickel precursor, which can reduce the sintering temperature, avoid destroying the crystal structure, maintain the consistency of the crystal structure, and improve the cycle performance and safety performance of the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a high-nickel precursor and a preparation method thereof, a positive electrode material, a secondary battery and electrical equipment. Background Art

[0002] Lithium-ion batteries are currently widely used in various fields such as new energy vehicles, portable mobile devices, and energy storage power supplies. The electrochemical performance of lithium-ion batteries depends largely on the performance of the positive electrode material. Among them, lithium-ion battery positive electrode materials prepared from high-nickel precursors have become one of the mainstream research directions of lithium-ion battery positive electrode materials because of their high energy density, long service life, high stability and other advantages.

[0003] However, due to the high nickel content in the current high-nickel precursor, the cycle performance and safety performance of the positive electrode material are reduced. Summary of the invention

[0004] The present application provides a high-nickel precursor and a preparation method thereof, a positive electrode material, a secondary battery and electrical equipment, which are used to solve the technical problems of reduced cycle performance and decreased safety performance of positive electrode materials made from high-nickel precursors.

[0005] According to a first aspect of the present invention, a high-nickel precursor is provided, wherein the ratio a of the molar amount of nickel in the high-nickel precursor to the total molar amount of metal contained in the high-nickel precursor is 0.90-1.00; the high-nickel precursor comprises secondary particles composed of primary particles, and the specific surface area BET of the high-nickel precursor is 25 m 2 / g-70m 2 / g, optional 25m 2 / g-50m 2 / g.

[0006] The molar amount of nickel in the high-nickel precursor provided in the present application accounts for 90%-100% of the molar amount of metal in the precursor. Compared with existing high-nickel products, its nickel content is higher, which is more conducive to improving the energy density and capacity performance of the positive electrode material prepared therefrom.

[0007] In addition, the high nickel precursor provided in this application has a large specific surface area, 25m 2 / g-70m 2 / g, optional 25m 2 / g-50m 2 / g. This indicates that it has a porous structure, which is beneficial to promote the sintering mass transfer process of the high-nickel precursor when preparing the positive electrode material, can reduce the sintering temperature, avoid destroying the crystal structure, maintain the consistency of the crystal structure, and improve the cycle performance and safety performance of the positive electrode material.

[0008] The BET test standard is: Determination of specific surface area of ​​metal powder-nitrogen adsorption method (GB / T 13390-2008).

[0009] In some embodiments of the present application, the porosity of the secondary particles is 49.70%-70%.

[0010] In some embodiments of the present application, the average pore size of the secondary particles is 30-300 nm, optionally 50-100 nm.

[0011] In some embodiments of the present application, the secondary particle has a full-pore structure consisting of three-dimensional pores from the inner layer to the outer layer.

[0012] In some embodiments of the present application, the sphericity R of the secondary particles is q It is 75%-100%, optional 85-95%.

[0013] In some embodiments of the present application, the particle size D50 of the secondary particles is 1.0-10.0 μm, and optionally 1.20-2.50 μm.

[0014] In some embodiments of the present application, the particle size distribution of the secondary particles is (D95-D5) / D50 is 0.3-1.5, and can be optionally 0.59-0.99.

[0015] In some embodiments of the present application, the (101) crystal plane grain size D of the secondary particles is 5-20 nm, and may be 10-18 nm.

[0016] In some embodiments of the present application, the deformation stacking fault rate FD of the secondary particles is 0-1.5%.

[0017] In some embodiments of the present application, the secondary particles are formed by cross-arrangement of the primary particles, the primary particles are composed of thin sheet units, and the thin sheet units are composed of nanosheets. Optionally, the length x of the nanosheet is 12nm-49nm, and the width y of the nanosheet is 7-49nm. Optionally, the aspect ratio x / y of the nanosheet is 0.95-3.05.

[0018] In some embodiments of the present application, the chemical formula of the high nickel precursor is Ni a Co b Mn c Me (1-a-b-c) (OH)2, wherein 0.90≤a≤1.00, 0≤b≤0.10, 0≤c≤0.10, 0.90≤a+b+c≤1.00, and the doped metal Me is one or more of W, Mg, Al, Ti, Y, Zr, Ca, Nb and La.

[0019] In some embodiments of the present application, the density ratio I of the high nickel precursor is 0.49-0.99, wherein the density ratio I=AD / TD, AD is the bulk density of the secondary particles of the high nickel precursor, and TD is the tap density of the secondary particles of the high nickel precursor.

[0020] According to a second aspect of the present invention, there is provided a method for preparing a high-nickel precursor, comprising:

[0021] A preparation step, preparing a base solution containing a precipitant and a complexing agent, wherein the pH of the base solution is 11.00 to 11.55, and heating the base solution;

[0022] A synthesis reaction step, wherein a metal salt solution, a precipitant solution and a complexing agent solution are simultaneously introduced into the base liquid, and a synthesis reaction is performed under an atmosphere of protective gas, wherein the pH of the synthesis reaction is maintained at 9.80 to 10.50 to obtain a mixed solution;

[0023] The separation step is to perform solid-liquid separation on the mixed liquid to obtain the high-nickel precursor.

[0024] In some embodiments of the present application, the metal salt is a nickel salt, a cobalt salt, a manganese salt, and a combination of doped metal salts containing at least a nickel salt.

[0025] In some embodiments of the present application, the sum of the mass concentrations of metal ions in the metal salt solution is 50-160 g / L, optionally 60-150 g / L, and more optionally 80-130 g / L.

[0026] In some embodiments of the present application, the precipitant includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.

[0027] In some embodiments of the present application, the mass percentage concentration of the precipitant solution is 1.0% to 50.0%, optionally 5.0% to 40.0%, and more preferably 10.0% to 30.0%.

[0028] In some embodiments of the present application, the complexing agent includes one or more of citric acid, sodium citrate, ammonium citrate, oxalic acid, ammonium oxalate, ammonia water, and ammonium carbonate.

[0029] In some embodiments of the present application, the mass percentage concentration of the complexing agent solution is 0.10% to 50.5%, optionally 1.0% to 40.0%, and more preferably 5.0% to 30.0%.

[0030] In some embodiments of the present application, in the preparation step, the base liquid is heated to 30-50°C.

[0031] In some embodiments of the present application, in the synthesis reaction step, the concentration of the complexing agent is 3.0 to 8.0 g / L, and optionally 3.0 to 6.0 g / L.

[0032] In some embodiments of the present application, in the synthesis reaction step, the temperature of the synthesis reaction is maintained at 30-50°C.

[0033] In some embodiments of the present application, in the synthesis reaction step, the base liquid is stirred at a rotation speed of 200-500 r / min, and optionally 300-450 r / min.

[0034] In some embodiments of the present application, in the synthesis reaction step, the introduction rate of the metal salt solution is 5-10% / h of the available volume of the reaction container.

[0035] In some embodiments of the present application, in the synthesis reaction step, the introduction rate of the precipitant solution is 1.5-5% / h of the available volume of the reaction container.

[0036] In some embodiments of the present application, in the synthesis reaction step, the introduction rate of the complexing agent solution is 0.05-0.5% / h of the available volume of the reaction container, and can be 0.1-0.2% / h.

[0037] According to a third aspect of the present invention, there is provided a positive electrode material, which is prepared from the above-mentioned high-nickel precursor.

[0038] According to a fourth aspect of the present invention, there is provided a secondary battery, comprising a positive electrode plate, wherein the positive electrode plate is made of the positive electrode material described above.

[0039] According to a fifth aspect of the present invention, there is provided an electrical device, the electrical device comprising the above-mentioned secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 A schematic diagram of the composition structure of the high nickel precursor provided in this application;

[0042] Figure 2 This is a SEM image (1000 times) of the high nickel precursor prepared in Example 1;

[0043] Figure 3This is the SEM image (50000 times) of the high nickel precursor prepared in Example 1;

[0044] Figure 4 CP cross-sectional view of the high nickel precursor prepared in Example 1;

[0045] Figure 5 This is an average pore distribution curve of the high nickel precursor prepared in Example 1;

[0046] Figure 6 This is the SEM image (50,000 times) of the precursor prepared in Comparative Example 1;

[0047] Figure 7 CP cross-sectional view of the precursor prepared in Comparative Example 1;

[0048] Figure 8 This is the SEM image (50,000 times) of the precursor prepared in Comparative Example 2;

[0049] Fig. 9 This is the CP cross-sectional view of the precursor prepared in Comparative Example 2. DETAILED DESCRIPTION

[0050] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0053] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0054] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may also include or contain other components not listed, or may only include or contain the listed components.

[0055] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0056] The present application provides a high-nickel precursor, wherein the ratio a of the molar amount of nickel to the total molar amount of metal contained in the high-nickel precursor is 0.90-1.00; the high-nickel precursor comprises secondary particles composed of primary particles, and the specific surface area of ​​the secondary particles is 25 m 2 / g-70m 2 / g, optional 25m 2 / g-50m 2 / g.

[0057] The molar amount of nickel in the high-nickel precursor provided in the present application accounts for 90%-100% of the molar amount of metal in the precursor. Compared with existing high-nickel products, its nickel content is higher, which is more conducive to improving the energy density and capacity performance of the positive electrode material prepared therefrom.

[0058] In addition, the high nickel precursor provided in this application has a large specific surface area, 25m 2 / g-70m 2 / g, optional 25m 2 / g-50m 2 / g. This indicates that it has a porous structure, which is beneficial to promote the sintering mass transfer process of the high-nickel precursor when preparing the positive electrode material, can reduce the sintering temperature, avoid destroying the crystal structure, maintain the consistency of the crystal structure, and improve the cycle performance and safety performance of the positive electrode material.

[0059] It should be noted that for the low-medium nickel series of precursor products, the manganese content is relatively high. By introducing air or liquid oxidants (such as hydrogen peroxide, etc.) as oxidizing aids, the manganese element in the precursor can be oxidized to easily increase the precursor specific surface area. As the nickel content in the product increases, the manganese content will decrease relatively. It is difficult to prepare a large specific surface area (greater than 25m 2 / g) of high nickel precursor products. The present invention adjusts the temperature, solution flow rate, pH value, etc. of the high nickel precursor reaction so that the primary particles in the precursor core present a specific morphology and structural composition, effectively increasing the specific surface area of ​​the precursor.

[0060] In some embodiments of the present application, the porosity of the secondary particles is 49.70%-70%.

[0061] In some embodiments of the present application, the average pore size of the secondary particles is 50-300 nm.

[0062] The high nickel precursor provided in the present application has a relatively large porosity of 49.70%-70% and an average pore size of 50-300nm, wherein the porosity can be selected to be 50%-65%, such as 50%-54%, 55%-58% and 60%-64%, etc., and the average pore size can be selected to be 80-260nm, such as 90-110nm, 120-150nm, 160-180nm, 200-220nm and 230-250nm, etc., so that after it is made into a positive electrode material, it is beneficial for the electrolyte to fully infiltrate the positive electrode material, thereby increasing the electron conduction rate, and improving the charge and discharge capacity and rate performance of the battery.

[0063] In some embodiments of the present application, the secondary particle has a full-pore structure consisting of three-dimensional pores from the inner layer to the outer layer.

[0064] The fully porous structure from inside to outside of the secondary particles is conducive to promoting the sintering mass transfer process of the high nickel precursor, reducing the sintering temperature, maintaining the consistency of the crystal structure, and improving the cycle performance and safety performance of the positive electrode material. The positive electrode material made of it can provide more electron reaction active sites and ion transmission channels during the charge and discharge process, which is conducive to the migration and transportation of electrons and improves the capacity performance of the positive electrode material.

[0065] In some embodiments of the present application, the sphericity R of the secondary particles is q It is 80%-100%.

[0066] The high-nickel precursor provided in the present application has a high sphericity of 80%-100%, optionally 90%-100%. After being made into a positive electrode material, the positive electrode material can have better compressive strength and a more stable structure during the charge and discharge cycle, which is beneficial to improving the cycle stability and safety performance of the positive electrode material.

[0067] In some embodiments of the present application, the particle size D50 of the secondary particles is 1.0-10.0 μm, optionally 1.20-2.50 μm.

[0068] The secondary particles of the high-nickel precursor provided in the present application have a smaller particle size D50 of 1.0-10.0μm, and can be optionally 1.20-2.50μm, such as 1.20-1.40μm, 1.50-1.70μm and 1.75-1.95μm, etc. After being made into the positive electrode material, it is beneficial to increase the contact area between the positive electrode material and the electrode liquid, give full play to the activity of the internal substances of the positive electrode material, and improve the capacity of the positive electrode material.

[0069] In some embodiments of the present application, the particle size distribution of the secondary particles is (D95-D5) / D50 is 0.3-1.5, and can be optionally 0.59-0.99.

[0070] The secondary particles of the high-nickel precursor provided in the present application have a uniform particle size distribution, and (D95-D5) / D50 is 0.59-0.99, and can be optionally 0.59-0.90, such as 0.59-0.80, 0.59-0.70 and 0.59-0.65, etc., indicating that the secondary particles have good consistency. After being made into positive electrode materials, the structure of the positive electrode materials can be made more stable, which is beneficial to improving the cycle stability of the positive electrode materials.

[0071] In some embodiments of the present application, the (101) crystal plane grain size D of the secondary particles is 5-20 nm, and optionally 10-18 nm.

[0072] The secondary particles of the high-nickel precursor provided in the present application have a suitable (101) crystal plane grain size of 5-20nm, optionally 10-18nm, so that after being made into a positive electrode material, the positive electrode material can maintain a low charge transfer activation energy during the charge and discharge reaction, which is beneficial to improving the capacity performance of the positive electrode material.

[0073] In some embodiments of the present application, the deformation stacking fault rate FD of the secondary particles is 0-1.5%.

[0074] The high-nickel precursor provided in the present application has a relatively small deformation stacking fault rate of 0-1.5%, optionally 0-1.0%, so that the positive electrode material prepared therefrom has good structural stability, can effectively improve the cycle performance of the positive electrode material during the charge and discharge process, and extend the service life of the battery.

[0075] In some embodiments of the present application, the secondary particles are formed by cross-arrangement of the primary particles, the primary particles are composed of thin sheet units, and the thin sheet units are composed of nanosheets. Optionally, the length x of the nanosheet is 12-49 nm; the width y of the nanosheet is 7-49 nm. Optionally, the aspect ratio x / y of the nanosheet is 0.95-3.05.

[0076] The high-nickel precursor provided in the present application has nanosheets of smaller size, and the nanosheets are used to form thin sheet units, which form primary particles, making it convenient for secondary particles to form a full-pore structure from the inside to the outside. After the positive electrode material is made, it is beneficial for the electrolyte to fully infiltrate the positive electrode material, so that the positive electrode material has more electronic reaction active sites and ion transmission channels during the charging and discharging process, which is beneficial to the migration and transportation of electrons and improves the capacity performance of the positive electrode material.

[0077] In some embodiments of the present application, the chemical formula of the high nickel precursor is Ni a Co b Mn c Me (1-a-b-c) (OH)2, wherein 0.90≤a≤1.00, 0≤b≤0.10, 0≤c≤0.10, 0.90≤a+b+c≤1.00, and the doped metal Me is one or more of W, Mg, Al, Ti, Y, Zr, Ca, Nb and La. A variety of elements may be doped to improve the electrochemical properties of the positive electrode material prepared therefrom.

[0078] In some embodiments of the present application, the density ratio I of the high nickel precursor is 0.49-0.99, wherein the density ratio I=AD / TD, AD is the bulk density of the secondary particles of the high nickel precursor, and TD is the tap density of the secondary particles of the high nickel precursor.

[0079] The high-nickel precursor provided in the present application has a large density ratio, so that the positive electrode material made therefrom has a large tap density, which is beneficial to improving the energy density of the positive electrode material.

[0080] In some embodiments of the present application, the impurity content of the high nickel precursor is low, MI is 0-10ppb, Na is 0-80ppm, S is 0-2000ppm, and H2O is 0-4000ppm, thereby effectively improving the safety and cycle stability of the positive electrode material made therefrom.

[0081] In order to fully disclose the above-mentioned precursor, the present application also provides a method for preparing the above-mentioned high-nickel precursor, which comprises:

[0082] S100, a preparation step, preparing a base solution containing a precipitant and a complexing agent, wherein the pH of the base solution is 11.00-11.55, and the base solution is heated.

[0083] S200, a synthesis reaction step, wherein a metal salt solution, a precipitant solution and a complexing agent solution are simultaneously introduced into the base liquid. A synthesis reaction is performed under a protective gas atmosphere, and the pH of the synthesis reaction is maintained at 9.80 to 10.50 to obtain a mixed solution;

[0084] S300, a separation step, performing solid-liquid separation on the mixed liquid to obtain a high-nickel precursor.

[0085] Among them, solid-liquid separation can be any method of separating solids and liquids well known in the art, for example, solid-liquid separation treatment can be carried out by centrifugation, tilting, filtration and other methods. In the preparation method provided in the present application, by pre-preparing a base liquid containing a precipitant and a complexing agent, a crystal nucleus of uniform size can be formed when a metal solution is subsequently passed. By adjusting the amount of precipitant and complexing agent added to the base liquid, the number of crystal nuclei can be controlled, thereby controlling the rate of subsequent synthesis reactions, and performing synthesis reactions to prepare secondary particles with a porous structure. Thereby, when preparing the positive electrode material therefrom, it is beneficial to promote the sintering mass transfer process of the high nickel precursor, reduce the sintering temperature, avoid destroying the crystal structure, and maintain the consistency of the crystal structure to improve the cycle performance and safety performance of the positive electrode material.

[0086] In some embodiments of the present application, the metal salt is a nickel salt, a cobalt salt, a manganese salt, and a combination of doped metal salts including at least a nickel salt.

[0087] The multiple combinations containing at least nickel salts should be understood as metal salts including nickel salts and at least one of cobalt salts, manganese salts and doped metal salts; wherein the nickel salts include one or more of nickel sulfate, nickel nitrate and nickel chloride, the cobalt salts include one or more of cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt carbonate, the manganese salts include one or more of manganese sulfate, manganese nitrate, manganese chloride and manganese carbonate, and the doped metal salts include one or more of sulfates, nitrates, hydrochlorides and carbonates of the corresponding doped metals.

[0088] In some embodiments of the present application, controlling the sum of the mass concentrations of metal ions in the metal salt solution, the concentration of the precipitant, and the concentration of the complexing agent within a certain range is beneficial to controlling the progress of the synthesis reaction.

[0089] Among them, the sum of the mass concentrations of metal ions in the metal salt solution is 50-160 g / L, optionally 60-150 g / L, and further optionally 80-130 g / L, such as 85 g / L, 90 g / L, 94 g / L, 102 g / L, 116 g / L, etc.

[0090] The precipitant includes one or more of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, and potassium carbonate solution. The mass percentage concentration of the precipitant solution is 1.0%-50.0%, and can be selected from 5.0% to 40.0%, and can further be selected from 10.0% to 30.0%, such as 10.2%, 14.1%, 22.4%, 28.8%, etc.

[0091] The complexing agent includes one or more of citric acid, sodium citrate, ammonium citrate, oxalic acid, ammonium oxalate, ammonia water, and ammonium carbonate. The mass percentage concentration of the complexing agent solution is 0.10% to 50.5%, and can be optionally 1.0% to 40.0%, and can further be optionally 5.0% to 30.0%, such as 6.2%, 8.5%, 14.3%, 23.6%, 28.7%, etc.

[0092] In some embodiments of the present application, in the preparation step, the pH and temperature of the base solution are maintained in a suitable range, which can provide suitable reaction conditions for the subsequent synthesis reaction, and the concentration of the complexing agent in the base solution is in a suitable range to facilitate the control of the reaction rate of the subsequent synthesis reaction. Among them, the pH of the base solution is 11.00-11.55, such as 11.10, 11.2, 11.3, 11.35, 11.45, etc.; the base solution is heated to 30-50°C, such as 38°C, 42°C, 46°C, etc.

[0093] In a further embodiment, in the synthesis reaction step, by controlling the pH of the mixed solution, the stirring speed of the bottom solution, the concentration of the complexing agent, the lower reaction temperature and the speed of the solution, the crystallization rate, morphological characteristics and structural composition of the prepared high nickel precursor can be effectively controlled, so that secondary particles with high nickel content, large specific surface area, high porosity and large average pore size can be prepared. Among them, the pH value of the mixed solution, the concentration of the complexing agent and the stirring speed are all key parameters affecting the morphology (including sphericity) and specific surface area (also including porosity) of the precursor. After adjusting the two parameters, the specific surface area and morphology of the prepared high nickel precursor will change greatly; the speed of adding the solution will affect the dispersion and growth of the precursor particles, and will also affect the sphericity of the precursor. Specifically, the pH of the synthesis reaction is maintained at 9.80-10.5, such as 10.00, 10.05, 10.15, 10.20, 10.30, 10.40, etc. The concentration of the complexing agent is 3.0-8.0 g / L, and can be 3.0-6.0 g / L, such as 3.5 g / L, 4.0 g / L, 4.5 g / L, 5.0 g / L, 5.4 g / L, etc. The temperature of the synthesis reaction is maintained at 30-50 ° C, such as 38 ° C, 42 ° C, 46 ° C, etc. The stirring speed of the bottom liquid is 200-500 r / min, and can be 300-450 r / min, such as 280 r / min, 340 r / min, 380 r / min, 420 r / min, etc. The introduction rate of the metal salt solution is 5-10% / h of the available volume of the reaction container, such as 6% / h, 7% / h, 8% / h, etc. The introduction rate of the precipitant solution is 1.5-5% / h of the available volume of the reaction container, such as 1.5% / h, 3.8% / h, 5.0% / h, etc. The introduction rate of the complexing agent solution is 0.05-0.5% / h of the available volume of the reaction container, and can be 0.1-0.2% / h, such as 0.12% / h, 0.18% / h, 0.2% / h, etc.

[0094] The present application provides a positive electrode material, which is made from the above-mentioned high-nickel precursor. Specifically, the positive electrode material is made by mixing and sintering the above-mentioned high-nickel precursor and a lithium source as raw materials, wherein the sintering temperature is 300-1000°C.

[0095] The present application uses a high nickel precursor with a porous structure as a raw material to prepare the positive electrode material, which is conducive to promoting the mass transfer process of sintering and reducing the sintering temperature. The sintering temperature can be maintained at 300-1000°C, 400-800°C, and further 500-600°C, such as 530°C, 555°C, 570°C, etc. This is conducive to maintaining the consistency of the crystal structure of the positive electrode material and improving the cycle performance and safety performance of the positive electrode material.

[0096] The present application provides a secondary battery, including a positive electrode plate, wherein the positive electrode plate is made of the above-mentioned positive electrode material, so that the secondary battery has higher rate performance, higher charge and discharge cycle stability and service life.

[0097] The present application provides an electrical device, which includes the secondary battery mentioned above.

[0098] In order to fully demonstrate the advantages of the high-nickel precursor provided by the present application, a description is given below in conjunction with specific embodiments.

[0099] Example 1

[0100] (1) Preparation of precursor

[0101] ① Prepare a metal salt solution with a metal ion mass concentration of 120 g / L as solution A, wherein the metal salts are nickel sulfate and cobalt sulfate, and the molar ratio of nickel to cobalt is Ni:Co=94:6; a sodium hydroxide solution with a mass percentage concentration of 20.5% as solution B; and an ammonia solution with a mass percentage concentration of 10.5% as solution C;

[0102] ② Add pure water, solution B and solution C into the reaction vessel to prepare the base solution, control the pH value of the base solution to 11.55, the mass concentration of ammonia water to 5.0 g / L, introduce nitrogen as a protective gas, and heat the base solution to 45°C.

[0103] ③ Solution A, solution B and solution C were introduced into the reaction vessel at the same time. The flow rates of solution A, B and C were 5% / h, 1.9% / h and 0.16% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 10.40, and the stirring device was controlled to stir at a speed of 300.35 r / min.

[0104] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 2.0 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.94 Co 0.06 High nickel precursor of (OH)2.

[0105] (2) Preparation of positive electrode materials

[0106] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.05, and sintered at 550° C. for 10 h to obtain a positive electrode material.

[0107] Example 2

[0108] (1) Preparation of precursor

[0109] ① Prepare a metal salt solution with a mass concentration of metal ions of 110 g / L as solution A, wherein the metal salts are nickel sulfate, cobalt sulfate, and manganese sulfate, and the molar ratio of nickel, cobalt, and manganese is Ni:Co:Mn=96:2:2; a sodium hydroxide solution with a mass percentage concentration of 15.9% as solution B; and an ammonia solution with a mass percentage concentration of 18.4% as solution C;

[0110] ② Add pure water, solution B and solution C into the reaction container to prepare the base solution, control the pH value of the base solution to 11.25, the mass concentration of ammonia water to 3.0 g / L, introduce argon as a protective gas, and heat the base solution to 50°C.

[0111] ③ Solution A, solution B and solution C were introduced into the reaction vessel at the same time. The flow rates of solution A, solution B and solution C were 10% / h, 4.0% / h and 0.15% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 10.10, and the stirring device was controlled to stir at a speed of 350.35 r / min.

[0112] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 1.9 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.96 Co 0.02 Mn 0.02 High nickel precursor of (OH)2.

[0113] (2) Preparation of positive electrode materials

[0114] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.10, and sintered at 540° C. for 12 h to obtain a positive electrode material.

[0115] Example 3

[0116] (1) Preparation of precursor

[0117] ① Prepare a metal salt solution with a mass concentration of 115 g / L of metal ions as solution A, wherein the metal salts are nickel sulfate, cobalt sulfate, and manganese sulfate, and the molar ratio of nickel, cobalt, and manganese is Ni:Co:Mn=94:4:2; prepare a sodium hydroxide solution with a mass percentage concentration of 17.4% as solution B; prepare an ammonia solution with a mass percentage concentration of 13.6% as solution C; prepare a solution doped with metal Zr with a mass concentration of 0.8 g / L as D;

[0118] ② Add pure water, solution B and solution C into the reaction vessel to prepare the base solution, control the pH value of the base solution to 11.35, the mass concentration of ammonia water to 3.8 g / L, introduce argon as a protective gas, and heat the base solution to 40°C.

[0119] ③ Solution A, solution B, solution C and solution D were introduced into the reaction vessel at the same time. The flow rates of solution A, B, C and D were 8% / h, 2.0% / h, 0.12% / h and 4% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 9.90, and the stirring device was controlled to stir at a speed of 400.35 r / min.

[0120] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 2.3 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.938 Co 0.038 Mn 0.017 Zr 0.007 High nickel precursor of (OH)2.

[0121] (2) Preparation of positive electrode materials

[0122] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.10, and sintered at 550° C. for 10 h to obtain a positive electrode material.

[0123] Example 4

[0124] (1) Preparation of precursor

[0125] ① Prepare a metal salt solution with a mass concentration of 120 g / L of metal ions as solution A, wherein the metal salts are nickel sulfate and cobalt sulfate, and the molar ratio of nickel to cobalt is Ni:Co=94:6; a sodium hydroxide solution with a mass percentage concentration of 20.5% as solution B; and an ammonia solution with a mass percentage concentration of 10.5% as solution C;

[0126] ② Add pure water, solution B and solution C into the reaction vessel to prepare the base solution, control the pH value of the base solution to 11.55, the mass concentration of ammonia water to 5.0 g / L, introduce argon as a protective gas, and heat the base solution to 45°C.

[0127] ③ Solution A, solution B and solution C were introduced into the reaction vessel at the same time. The flow rates of solution A, B and C were 5% / h, 1.9% / h and 0.16% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 10.40, and the stirring device was controlled to stir at a speed of 250.35 r / min.

[0128] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 2.0 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.94 Co 0.06 High nickel precursor of (OH)2.

[0129] (2) Preparation of positive electrode materials

[0130] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.05, and sintered at 550° C. for 12 h to obtain a positive electrode material.

[0131] Example 5

[0132] (1) Preparation of precursor

[0133] ① Prepare a metal salt solution with a metal ion mass concentration of 120 g / L as solution A, wherein the metal salts are nickel sulfate and cobalt sulfate, and the molar ratio of nickel to cobalt is Ni:Co=94:6; a sodium hydroxide solution with a mass percentage concentration of 20.5% as solution B; and an ammonia solution with a mass percentage concentration of 10.5% as solution C;

[0134] ② Add pure water, solution B and solution C into the reaction vessel to prepare the base solution, control the pH value of the base solution to 11.55, the mass concentration of ammonia water to 8.0 g / L, introduce nitrogen as a protective gas, and heat the base solution to 45°C.

[0135] ③ Solution A, solution B and solution C were introduced into the reaction vessel at the same time. The flow rates of solution A, solution B and solution C were 5% / h, 1.9% / h and 0.30% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 10.40, and the stirring device was controlled to stir at a speed of 300.35 r / min.

[0136] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 2.0 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.94 Co 0.06 High nickel precursor of (OH)2.

[0137] (2) Preparation of positive electrode materials

[0138] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.05, and sintered at 550° C. for 10 h to obtain a positive electrode material.

[0139] Comparative Example 1

[0140] (1) Preparation of precursor

[0141] ① Prepare a metal salt solution with a metal ion mass concentration of 120 g / L as solution A, wherein the metal salts are nickel sulfate and cobalt sulfate, and the molar ratio of nickel to cobalt is Ni:Co=94:6; a sodium hydroxide solution with a mass percentage concentration of 20.5% as solution B; and an ammonia solution with a mass percentage concentration of 10.5% as solution C;

[0142] ② Add pure water, solution B and solution C into the reaction vessel to prepare the base solution, control the pH value of the base solution to 11.55, the mass concentration of ammonia water to 5.0 g / L, introduce nitrogen as a protective gas, and heat the base solution to 45°C.

[0143] ③ Solution A, solution B and solution C were introduced into the reaction vessel at the same time. The flow rates of solution A, solution B and solution C were 5% / h, 2.0% / h and 0.16% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 10.80, and the stirring device was controlled to stir at a speed of 300.35 r / min.

[0144] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 2.0 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.94 Co 0.06 High nickel precursor of (OH)2.

[0145] (2) Preparation of positive electrode materials

[0146] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.05, and sintered at 550° C. for 10 h to obtain a positive electrode material.

[0147] Comparative Example 2

[0148] (1) Preparation of precursor

[0149] ① Prepare a metal salt solution with a mass concentration of metal ions of 110 g / L as solution A, wherein the metal salts are nickel sulfate, cobalt sulfate, and manganese sulfate, and the molar ratio of nickel, cobalt, and manganese is Ni:Co:Mn=96:2:2; a sodium hydroxide solution with a mass percentage concentration of 15.9% as solution B; and an ammonia solution with a mass percentage concentration of 18.4% as solution C;

[0150] ② Add pure water, solution B and solution C into the reaction container to prepare the base solution, control the pH value of the base solution to 11.25, the mass concentration of ammonia water to 8.0 g / L, introduce argon as a protective gas, and heat the base solution to 50°C.

[0151] ③ Solution A, solution B and solution C were introduced into the reaction vessel at the same time. The flow rates of solution A, solution B and solution C were 10% / h, 4.0% / h and 0.25% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 10.10, and the stirring device was controlled to stir at a speed of 350.35 r / min.

[0152] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 1.9 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.96 Co 0.02 Mn 0.02 High nickel precursor of (OH)2.

[0153] (2) Preparation of positive electrode materials

[0154] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.10, and sintered at 540° C. for 12 h to obtain a positive electrode material.

[0155] Comparative Example 3

[0156] (1) Preparation of precursor

[0157] ① Prepare a metal salt solution with a metal ion mass concentration of 120 g / L as solution A, wherein the metal salts are nickel sulfate and manganese sulfate, and the molar ratio of nickel to manganese is Ni:Co:Mn=80:10:10; a sodium hydroxide solution with a mass percentage concentration of 20.5% as solution B; and an ammonia solution with a mass percentage concentration of 10.5% as solution C;

[0158] ② Add pure water, solution B and solution C into the reaction vessel to prepare the base solution, control the pH value of the base solution to 11.85, the mass concentration of ammonia water to 5.0 g / L, introduce nitrogen as a protective gas, and heat the base solution to 45°C.

[0159] ③ Solution A, solution B and solution C were introduced into the reaction vessel at the same time. The flow rates of solution A, B and C were 5% / h, 1.9% / h and 0.16% / h of the available volume of the reaction vessel, respectively. The reaction was carried out under a protective gas atmosphere. During the reaction, the pH of the mixed solution was controlled to be maintained at 10.40, and the stirring device was controlled to stir at a speed of 300.35 r / min.

[0160] ④ The reaction is continued until the particle size D50 of the synthesized particles reaches 2.0 μm, and the solid-liquid separation is performed to obtain a precipitate. After washing, drying and sieving the precipitate, a product with the chemical formula Ni 0.80 Co 0.10 Mn 0.10 High nickel precursor of (OH)2.

[0161] (2) Preparation of positive electrode materials

[0162] The obtained precursor was evenly mixed with lithium hydroxide in a ratio of 1:1.05, and sintered at 550° C. for 10 h to obtain a positive electrode material.

[0163] Test Data

[0164] 1. Physical and chemical properties

[0165] In this application, porosity is a parameter that characterizes the morphology of particles, and its calculation formula is regional porosity = regional pore area S0 / regional total area S1×100%. Take several (such as 5) CP images, and select multiple (≥20) regions in the CP image to calculate the average porosity of multiple regions in one CP image, and then average the average porosity of each CP image as the final porosity. Among them, the section is a SEM image (such as 3000×) taken by a field emission scanning electron microscope (HITACHI SU8100), and the region is a partial section selected in the SEM image using Image J software.

[0166] The average pore size in this application is a parameter characterizing the pores, which is calculated through the nitrogen adsorption-desorption curve of the pores.

[0167] In the present application, the aspect ratio is a parameter that characterizes the morphology of primary particles. Nano Measurer software is used to measure the length and width of primary particles on the surface of secondary particles in an SEM image of a certain magnification (such as 3000×). The longest axis of a single primary particle is regarded as its length, and the short axis measured perpendicular to the midpoint of the longest axis is regarded as its width. At least 10 groups of single primary particle data are taken and the average value is taken to obtain the average width and average length of the primary particles, and the average aspect ratio is calculated. Then, several (such as 5) SEM images are taken for calculation, and the average value is taken as the final aspect ratio.

[0168] In the present application, sphericity is a parameter for characterizing the morphology of particles. A field emission scanning electron microscope (HITACHISU8100) is used to take multiple (e.g., 5) SEM images of a certain magnification (e.g., 3000×), and the sphericity software Avizo is used to calculate the formula: Sphericity = (4π×area) / (circumference×circumference)×100%. The sphericity in each SEM image is analyzed, and then the sphericity of several (e.g., 5) SEM images is averaged as the final sphericity.

[0169] In the present application, the grain size D of the (101) crystal plane is calculated using the Debye-Scherrer formula (D = (K*γ)(B*cosθ)), where the Scherrer constant K = 0.89, the ray wavelength γ = 0.154 nm, B represents the half-peak width of the corresponding peak in the XRD pattern, and θ is the angle corresponding to the half-peak width.

[0170] In the present application, the deformation stacking fault rate FD is calculated using the formula (FD = 0.16 × FWHM (101) - 0.032 × FWHM (102) - 0.44 / FWHM (001)). Wherein, FWHM (101) is the half-peak width of the X-ray diffraction spectrum of the high-nickel precursor (101) crystal plane, FWHM (102) is the half-peak width of the X-ray diffraction spectrum of the high-nickel precursor (102) crystal plane, and FWHM (001) is the half-peak width of the X-ray diffraction spectrum of the high-nickel precursor (001) crystal plane, and the unit is degree.

[0171] The physicochemical properties of the high nickel precursors prepared in the above-mentioned embodiments and comparative examples are shown in Tables 1 and 2.

[0172] Table 1 Physical and chemical data of high nickel precursors prepared in various embodiments and comparative examples

[0173]

[0174]

[0175] Table 2 Physical and chemical data of high nickel precursors prepared in various embodiments and comparative examples

[0176]

[0177] 2. Electrochemical performance

[0178] In this application, a button-type semi-electric battery is used for electrochemical performance testing. The positive electrode materials prepared in the above embodiments and comparative examples are mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a ratio of 8:1:1 to form a slurry, which is coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet uses a metal lithium sheet, and the electrolyte uses 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1). In a vacuum glove box, the battery shell, positive electrode sheet, negative electrode sheet, diaphragm, spring sheet, and gasket are assembled into a button battery. The electrochemical performance test is carried out using a blue electric test system.

[0179] At room temperature, a 0.3C charge-discharge test and a 1C (1C=210 mA / g) cycle 50-cycle test were performed at 3.0-4.3V. Please refer to Table 3 for the electrochemical properties of the positive electrode materials prepared in each embodiment and comparative example.

[0180] Table 3 Electrochemical performance test data of the positive electrode materials prepared in each embodiment and comparative example

[0181]

[0182] Please refer to Tables 1 to 3 and Figure 1-Figure 9As shown, the high nickel precursors prepared in Examples 1-5 all have large specific surface area, average porosity, pore size and BET / D50 ratio, which can provide more pore structures, which are beneficial to promote the sintering mass transfer process, reduce the sintering temperature when preparing the positive electrode material, and maintain the consistency of its crystal structure; so that after the battery is made, the positive electrode material has a more stable structure, which can improve its cycle performance and safety performance; further, more pore structures are also beneficial to improve the rate performance of the positive electrode material, so that it not only has a higher 0.3C first discharge capacity, but also has a higher rate performance and capacity retention rate. Therefore, the positive electrode material prepared based on the high nickel precursor provided in this application has a higher first charge and discharge gram specific capacity, first coulomb efficiency, rate performance and cycle capacity retention rate.

[0183] In the embodiment, the cathode material prepared by the present invention in the preferred embodiment 3 has a larger specific surface area, average porosity, pore size and BET / D50 ratio, which can provide more pore structures, which is conducive to promoting the sintering mass transfer process, greatly reducing the sintering temperature of the cathode material, and maintaining the consistency of the crystal structure; during the charge and discharge process, a more stable structure can improve its cycle performance and safety performance; more pore structures are also conducive to improving rate performance. Therefore, it not only has a higher 0.3C first discharge capacity, but also has a higher rate performance and capacity retention rate.

[0184] In Example 4, the sphericity is lower than that in Example 1, and the other indicators are close to those in Example 1. Its discharge capacity performance, coulombic efficiency and rate performance are also close to those in Example 1, while the cycle performance deviates from that in Example 1, indicating that the higher sphericity leads to better compressive strength and more stable structure during the cycle, which is conducive to improving the cycle stability performance.

[0185] In Example 5, its average porosity is lower than that in Example 1, and the other indicators are close to those in Example 1. Its discharge specific capacity performance is significantly lower than that in Example 1, and its coulombic efficiency, rate performance and cycle performance are close to those in Example 1. This shows that a larger pore size is more conducive to the migration and transport of electrons, which is conducive to the full infiltration of the electrolyte in the battery, improves the electron conduction rate, and is conducive to improving the charge and discharge capacity.

[0186] It can be seen from Examples 1 to 3 that the positive electrode based on the high nickel, large specific surface area, small particle size precursor positive electrode material prepared according to the present invention has a relatively high first charge and discharge gram-specific capacity, first coulombic efficiency, rate performance and cycle capacity retention rate.

[0187] Comparative Examples 1 to 2 use precursors prepared by traditional methods, which do not have the special structure and physicochemical properties of the present invention, resulting in the inability of the positive electrode materials prepared therefrom to simultaneously take into account the first charge and discharge gram-to-gram capacity, the first coulomb efficiency, and the cycle capacity retention rate. Specifically, compared with Example 1, the specific surface area of ​​the precursor of Comparative Example 1 is significantly smaller than that of Example 1. Although the positive electrode material prepared therefrom has a higher charge and discharge capacity, the cycle capacity retention rate and rate performance are significantly lower than those of Example 1; compared with Example 2, the specific surface area, average porosity, and pore size of Comparative Example 2 are significantly smaller. The positive electrode material prepared therefrom has a significantly lower first charge and discharge capacity, rate performance, and capacity retention rate after 50 cycles of 1C than Example 2.

[0188] Comparative Example 3 uses the method provided in the application to prepare the precursor, and the Ni content is significantly lower than that of Example 1, and the specific surface area is higher than that of Example 1. It is a low-nickel and high-specific surface product, and the positive electrode material made from it has significantly lower charge and discharge capacity, and the rate performance is also significantly lower than that of Example 1.

[0189] Finally, it should be noted that the various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.

[0190] In addition, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A high nickel precursor, characterized in that: The ratio a of the nickel molar amount of the high-nickel precursor to the total molar amount of metal contained in the high-nickel precursor is 0.90-1.00; the high-nickel precursor includes secondary particles composed of primary particles, and the specific surface area BET of the high-nickel precursor is 25m 2 / g-70m 2 / g.

2. The high nickel precursor according to claim 1, characterized in that The porosity of the secondary particles is 49.70%-70%; and / or, the average pore size of the secondary particles is 30-300 nm, preferably 50-100 nm; and / or, the secondary particles have a sphericity of 75% to 100%, preferably 85 to 95%; and / or, the particle size D50 of the secondary particles is 1.0-10.0 μm, preferably 1.20-2.50 μm; and / or, the particle size distribution (D95-D5) / D50 of the secondary particles is 0.3-1.5, preferably 0.59-0.99; and / or, the (101) crystal plane grain size D of the secondary particles is 5-20 nm, preferably 10-18 nm; And / or, the deformation stacking fault rate FD of the secondary particles is 0-1.5%.

3. The high nickel precursor according to claim 1 or 2, characterized in that: The secondary particles are formed by cross-arrangement of the primary particles, the primary particles are composed of thin sheet units, and the thin sheet units are composed of nanosheets; Preferably, the length x of the nanosheet is 12-49 nm; the width y of the nanosheet is 7-49 nm; Preferably, the aspect ratio x / y of the nanosheet is 0.95-3.05; And / or, the chemical formula of the high nickel precursor is Ni a Co b Mn c Me (1-a-b-c) (OH)2, wherein 0.90≤a≤1.00, 0≤b≤0.10, 0≤c≤0.10, 0.90≤a+b+c≤1.00, and the doped metal Me is one or more of W, Mg, Al, Ti, Y, Zr, Ca, Nb and La.

4. The high nickel precursor according to claim 3, characterized in that The density ratio I of the high nickel precursor is 0.49-0.99, wherein the density ratio I=AD / TD, AD is the bulk density of the secondary particles of the high nickel precursor, and TD is the tap density of the secondary particles of the high nickel precursor.

5. A method for preparing a high nickel precursor according to any one of claims 1 to 4, characterized in that: include: A preparation step, preparing a base solution containing a precipitant and a complexing agent, wherein the pH of the base solution is 11.00 to 11.55, and heating the base solution; A synthesis reaction step, wherein a metal salt solution, a precipitant solution and a complexing agent solution are simultaneously introduced into the base liquid, and a synthesis reaction is performed under an atmosphere of protective gas, wherein the pH of the synthesis reaction is maintained at 9.80 to 10.50 to obtain a mixed solution; The separation step is to perform solid-liquid separation on the mixed liquid to obtain the high-nickel precursor.

6. The method for preparing a high nickel precursor according to claim 5, characterized in that: The metal salt is a nickel salt, a cobalt salt, a manganese salt, and a combination of doped metal salts containing at least a nickel salt; And / or, the sum of the mass concentrations of metal ions in the metal salt solution is 50-160 g / L, preferably 60-150 g / L, more preferably 80-130 g / L; And / or, the precipitant includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate; And / or, the mass percentage concentration of the precipitant solution is 1.0% to 50.0%, preferably 5.0% to 40.0%, more preferably 10.0% to 30.0%; And / or, the complexing agent includes one or more of citric acid, sodium citrate, ammonium citrate, oxalic acid, ammonium oxalate, ammonia water, and ammonium carbonate; And / or, the mass percentage concentration of the complexing agent solution is 0.10% to 50.5%, preferably 1.0% to 40.0%, and more preferably 5.0% to 30.0%.

7. The method for preparing a high nickel precursor according to claim 6, characterized in that: In the preparation step, the base liquid is heated to 30-50°C; and / or, in the synthesis reaction step, the concentration of the complexing agent is 3.0 to 8.0 g / L, preferably 3.0 to 6.0 g / L; and / or, in the synthesis reaction step, the temperature of the synthesis reaction is maintained at 30 to 50° C.; and / or, in the synthesis reaction step, stirring the base liquid at a speed of 200-500 r / min, preferably 300-450 r / min; and / or, in the synthesis reaction step, the metal salt solution is introduced at a rate of 5 to 10% / h of the available volume of the reaction container; and / or, in the synthesis reaction step, the introduction rate of the precipitant solution is 1.5 to 5% / h of the available volume of the reaction container; And / or, in the synthesis reaction step, the introduction rate of the complexing agent solution is 0.05-0.5% / h, preferably 0.1-0.2% / h of the available volume of the reaction container.

8. A positive electrode material, characterized in that It is prepared from the high-nickel precursor according to any one of claims 1 to 4.

9. A secondary battery, comprising a positive electrode plate, characterized in that: The positive electrode sheet is made of the positive electrode material according to claim 8.

10. An electrical equipment, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Cited By

  • High-nickel positive electrode material precursor with narrow peak of core layer matched with wide peak of shell layer and preparation method of high-nickel positive electrode material precursor

    CN121672606A